2005
DOI: 10.4049/jimmunol.175.9.5857
|View full text |Cite
|
Sign up to set email alerts
|

A Defect in Deletion of Nucleosome-Specific Autoimmune T Cells in Lupus-Prone Thymus: Role of Thymic Dendritic Cells

Abstract: To study central tolerance to the major product of ongoing apoptosis in the thymus, we made new lines of transgenic (Tg) mice expressing TCR of a pathogenic autoantibody-inducing Th cell that was specific for nucleosomes and its histone peptide H471–94. In the lupus-prone (SWR × NZB)F1 (SNF1) thymus, introduction of the lupus TCR transgene caused no deletion, but marked down-regulation of the Tg TCR and up-regulation of endogenous TCRs. Paradoxically, autoimmune disease was suppressed in the αβTCR Tg SNF1 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 61 publications
2
15
0
Order By: Relevance
“…It was first confirmed that DCs induce immune tolerance in the central self-tolerance. Existing studies show that the injection of allogeneic DCs into the thymus of newborn mice induces immune tolerance (Michaels et al, 2005). Similar results were obtained in studies of bone marrow chimeras and transgenic mice.…”
Section: Discussionsupporting
confidence: 71%
“…It was first confirmed that DCs induce immune tolerance in the central self-tolerance. Existing studies show that the injection of allogeneic DCs into the thymus of newborn mice induces immune tolerance (Michaels et al, 2005). Similar results were obtained in studies of bone marrow chimeras and transgenic mice.…”
Section: Discussionsupporting
confidence: 71%
“…Self antigens (e.g. hemoglobin, C5 component of the complement pathway, lysozyme, and apoptotic nucleosomes) are constitutively processed and presented by antigen-presenting cells (APCs) [90,101,105,116,124,129,167,194,203]. Therefore, self determinants can also be categorized as dominant and non-dominant.…”
Section: Tolerogenicity Of Self Antigens In the Context Of The Determmentioning
confidence: 99%
“…301,308 This further suggested that a defect in Treg numbers or function may contribute to lupus pathogenesis. Moreover, it has been found that administration of tolerogenic peptides, such as pCons from anti-DNA IgG in NZB/W F1 mice 309 or histone peptide H471 in SNF1 mice, 310 ameliorated disease by expanding the Treg subset. Clearly, modulating Treg number and function might be a promising way to treat human SLE.…”
Section: B T-cell Tolerancementioning
confidence: 99%